ผลการใช้ชุดกิจกรรมเพื่อพัฒนาความคิดเชิงบวกแก่กลุ่มผู้ต้องขังเรือนจำกลางบางขวาง จังหวัดนนทบุรี - แก่นตาคำ สวงค์; วงษ์ทิม สุขอรุณ (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2017)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ 1) เปรียบเทียบความคิดเชิงบวกของผู้ต้องขังกลุ่มทดลองก่อนและหลังการใช้ชุดกิจกรรมแนะแนว 2) เปรียบเทียบความคิดเชิงบวกหลังการทดลองของผู้ต้องขังกลุ่มทดลองและกลุ่มควบคุม และ 3) ศึกษาความพึงพอใจที่มีต่อชุดกิจกรรมแนะแนวเพื่อพัฒนาความคิดเชิงบวก รูปแบบการวิจัยเป็นการวิจัยกึ่งทดลอง ตัวอย่างเป็นผู้ต้องขังเรือนจำกลางบางขวาง แดน 2 จังหวัดนนทบุรี จำนวน 30 คน มีคะแนนจากแบบวัดความคิดเชิงบวกต่ำกว่าเปอร์เซ็นไทล์ที่ 50 และสมัครใจเข้าร่วมการทดลอง จากนั้นจึงสุ่มอย่างง่ายเพื่อแบ่งเป็นกลุ่มทดลองและกลุ่มควบคุม กลุ่มละ 15 คน เครื่องมือที่ใช้ในการวิจัย ได้แก่ 1) แบบวัดความคิดเชิงบวก มีค่าความเที่ยงเท่ากับ .94 2) ชุดกิจกรรมแนะแนวเพื่อพัฒนาความคิดเชิงบวก และ 3) แบบวัดความพึงพอใจต่อชุดกิจกรรมเพื่อพัฒนาความคิดเชิงบวก สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน และการทดสอบค่าที ผลการวิจัย พบว่า 1) ภายหลังการทดลองผู้ต้องขังกลุ่มทดลองที่ได้รับการใช้ชุดกิจกรรมแนะเพื่อพัฒนาความคิดเชิงบวกมีความคิดเชิงบวกเพิ่มสูงขึ้นกว่าก่อนการทดลองอย่างมีนัยสำคัญทางสถิติที่ระดับ .01 2) ภายหลังการทดลองผู้ต้องขังกลุ่มทดลองมีความคิดเชิงบวกสูงกว่าผู้ต้องขังกลุ่มควบคุมอย่างมีนัยสำคัญทางสถิติที่ระดับ.01 และ 3) ความพึงพอใจต่อชุดกิจกรรมแนะแนวเพื่อพัฒนาความคิดเชิงบวกของผู้ต้องขังกลุ่มทดลองอยู่ในระดับมาก THE EFFECTS OF USING A GUIDANCE ACTIVITIES PACKAGE TO DEVELOP POSITIVE THINKING FOR PRISONERS IN BANG KWANG CENTRAL PRISON, NONTHABURI PROVINCE Abstract The objective of this research were to 1) compare positive thinking in an experimental group of prisoners before and after using a guidance activities package, 2) compare positive thinking after using the guidance activities package of the experimental group and a control group, and 3) study the satisfaction on the guidance activities package to develop positive thinking. This research design was quasi-experimental. Sample consisted 30 prisoners in Bang Kwang Central Prison building 2, Nonthaburi province whose scores from positive thinking questionnaires were below 50 percentile and they volunteered into the study. Then, they were randomly assigned into the experimental group and control group, each of which containing 15 persons. The instruments were 1) the positive thinking questionnaires with Cronbach’s alpha coefficient reliability of .94, 2) the guidance activities package to develop positive thinking, and 3) the satisfaction questionnaires on the guidance activities package to develop positive thinking. Data were analyzed by mean, standard deviation, and t-test. The findings revealed that 1) after experiment, the experimental group of prisoners who received the guidance activities package had positive thinking significantly higher than their pre-experiment score at .01 level, 2) after experiment, the experimental group had positive thinking significantly higher than the control group at the .01 level, and 3) satisfaction on the guidance activities package was in high level.